The dynamical evolution of molecular clouds near the Galactic Centre: III. Tidally induced star formation in protocluster clouds - Dale, James; Kruijssen, Diederik; Longmore, Steven N. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. As part of a series of papers aimed at understanding the evolution of the Milky Way’s Central Molecular Zone (CMZ), we present hydrodynamical simulat